Changing understandings of waste reduction and avoidance in moralities of thrift: A comparison of Mass Observers' narratives three decades apart. Issue 137 (December 2022) - Ehgartner, Ulrike; Holmes, Helen
Highlights: Waste reduction and avoidance are key to understandings of thrift. How motivations for thrift are explained depends on their temporal context. Thrift as the preservation of economic resources is seen as something from the past. Moralities of thrift change with the rise of single use products and packaging. Municipal waste management and infrastructures impact understandings of thrift. Abstract: This paper explores shifting ideas of waste and recycling in narratives on thrift in the UK. Drawing on texts written by 33 respondents who answered two separate Mass Observation Directives on the subject of thrift in 1987 and 2016, it illuminates how waste reduction and avoidance is described by 'ordinary people'. The ways in which these practices are framed are dependent on the temporal context in which the narrative is set. Two key findings are presented. Firstly, respondents explain motivations for such practices differently, depending on whether their examples relate to what they were exposed to during their upbringing or to their own practices at present. Between these two contexts, the moralisation of thrift through practices of waste reduction and avoidance shifts from a focus on financial hardship towards consciousness/satisfaction, which indicates that current understandings of thrift combine values of ethical consumerism and hedonism. Secondly, responses to the 1987 and 2016 directives differ in terms of how thrift through waste reduction and avoidance of disposable items is accounted for. In 1987 writings, thrift was associated with efforts to find ways to use single-use multiple times, whereas in the 2016 writings, thrift is associated with a firm commitment to household waste recycling through municipal services. This indicates that since the 1980s, material and infrastructural changes have led to a shift of norms in dealing with single-use products and recycling. The findings point towards critical considerations of how moralities of thrift are employed in the context of material culture in the 21st century.